Disease-free Survival and Local Recurrence for Laparoscopic Resection Compared With Open Resection of Stage II to III Rectal Cancer: Follow-up Results of the ACOSOG Z6051 Randomized Controlled Trial. Issue 4 (April 2019) - Fleshman, James; Branda, Megan E.; Sargent, Daniel J.; Boller, Anne Marie; George, Virgilio V.; Abbas, Maher A.; Peters, Walter R.; Maun, Dipen C.; Chang, George J.; Herline, Alan; Fichera, Alessandro; Mutch, Matthew G.; et al.
Abstract : Objective: To determine the disease-free survival (DFS) and recurrence after the treatment of patients with rectal cancer with open (OPEN) or laparoscopic (LAP) resection. Background: This randomized clinical trial (ACOSOG [Alliance] Z6051), performed between 2008 and 2013, compared LAP and OPEN resection of stage II/III rectal cancer, within 12 cm of the anal verge (T1-3, N0-2, M0) in patients who received neoadjuvant chemoradiotherapy. The rectum and mesorectum were resected using open instruments for rectal dissection (included hybrid hand-assisted laparoscopic) or with laparoscopic instruments under pneumoperitoneum. The 2-year DFS and recurrence were secondary endpoints of Z6051. Methods: The DFS and recurrence were not powered, and are being assessed for superiority. Recurrence was determined at 3, 6, 9, 12, and every 6 months thereafter, using carcinoembryonic antigen, physical examination, computed tomography, and colonoscopy. In all, 486 patients were randomized to LAP (243) or OPEN (243), with 462 eligible for analysis (LAP = 240 and OPEN = 222). Median follow-up is 47.9 months. Results: The 2-year DFS was LAP 79.5% (95% confidence interval [CI] 74.4–84.9) and OPEN 83.2% (95% CI 78.3–88.3). Local and regional recurrence was 4.6% LAP and 4.5% OPEN. Distant recurrence was 14.6% LAP and 16.7% OPEN. Disease-free survival was impacted by unsuccessful resection (hazard ratio [HR] 1.87, 95% CI 1.21–2.91): composite of incomplete specimen (HR 1.65, 95% CI 0.85–3.18); positive circumferential resection margins (HR 2.31, 95% CI 1.40–3.79); positive distal margin (HR 2.53, 95% CI 1.30–3.77). Conclusion: Laparoscopic assisted resection of rectal cancer was not found to be significantly different to OPEN resection of rectal cancer based on the outcomes of DFS and recurrence. Abstract : Supplemental Digital Content is available in the text